Regional Trade Agreements, conflits and Welfare - (:unkn) unknown (My University, 2019)
This thesis aims to contribute to recent debates on the potential benefits of trade openness among African countries. This, by addressing the triptych regional trade agreements, welfare and conflict.The African continent is currently facing two major governance challenges: regional integration and the management of armed conflicts. Indeed, the trade performance of African countries remains marginal compared to the rest of the world. This is despite the different trade policies implemented since the 1970s (import substitution policy, North-South regional agreement, etc.). Among these trade policies, African governments have decided to focus on regional agreements in order to increase trade among member countries. Have these agreements had the expected effect ? To what extent ?If we refer to popular belief, the answer seems to be no. However, this answer ignores the potential political benefits of trade openness. As such, the work presented here first examines the effect of African regional agreements on trade and welfare. This is done using the latest developments in international trade theory and the best techniques for estimating gravity equations. Second, we analyze both theoretically and empirically the effect of increased trade on the probability of a civil war occurring. The results obtained allow us to conclude, on the one hand, that nearly half of the trade between members of trade agreements in Africa would not have been possible without the signing of the RTAs. On the other hand, both domestic and international trade, reduces the risk of civil conflict in Africa.
Keywords: African Research